PROCEEDINGS OF 46TH ANNUAL MEETING OF INDIAN PHYTOPATHOLOGICAL SOCIETY, COIMBATORE, JANUARY 27-29, 1994 - IPS, Editor (Indian Phytopathology, 2002)
ABSTRACT OF PAPERS - NATIONAL SYMPOSIUMULTRASTRUCTURE, CYTOLOGY, SEXUALITY AND VARIABILITY IN PLANT PATHOGENS